2016
DOI: 10.1093/aje/kwv454
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Long-Term Association of Personality With Cause-Specific Mortality in London: Four Decades of Mortality Surveillance in the Original Whitehall Smoking Cessation Trial

Abstract: The personality domains of extraversion and neuroticism are regarded as being stable individual psychological characteristics, yet it remains unclear whether they are associated with chronic disease over an extended period of time. In a randomized controlled trial of smoking cessation nested within the original prospective Whitehall Study , the Eysenck Personality Questionnaire was administered to 832 male self-declared smokers who had undergone a medical examination during which their levels of extraversion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…In our models that controlled for other factors that elevate the risk for premature death, there was no association between adolescent tolerance for deviance and tobacco-specific mortality, but adolescents who were less tolerant of deviance were more likely to die prematurely of any cause in our sample. Although this finding was in the unexpected direction, previous studies, including meta-analyses, have found no direct association between personality and mortality (Batty et al, 2016;Jokela et al, 2013;Jokela et al, 2014). Indeed, the zero-order correlations from the current data indicated no prospective relation between tolerance for deviance in adolescence and either mortality outcome.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In our models that controlled for other factors that elevate the risk for premature death, there was no association between adolescent tolerance for deviance and tobacco-specific mortality, but adolescents who were less tolerant of deviance were more likely to die prematurely of any cause in our sample. Although this finding was in the unexpected direction, previous studies, including meta-analyses, have found no direct association between personality and mortality (Batty et al, 2016;Jokela et al, 2013;Jokela et al, 2014). Indeed, the zero-order correlations from the current data indicated no prospective relation between tolerance for deviance in adolescence and either mortality outcome.…”
Section: Discussioncontrasting
confidence: 85%
“…These included educational attainment, other tobacco use, physical activity, healthy eating, and seat belt use. Previous studies testing predictors of elevated mortality risk have similarly included demographic factors and engagement in other healthy and risky behaviors as covariates (Batty et al, 2016;Inoue-Choi et al, 2016;Khan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating personality traits in general observed for all-cause mortality an association with conscientiousness only (31)(32)(33). For CVD mortality, there was evidence for a positive association with neuroticism (12,34), anger, and hostility (35).…”
Section: Discussionmentioning
confidence: 97%
“…Only few studies restricting to males (6,10,26,27,33) or females (32) presented sex-specific figures, however without finding significant associations. The sex-specific results in the competitiveness subscale that we found might be partly explained by a greater likelihood of CVD events induced by postmenopausal hormone replacement therapy (40).…”
mentioning
confidence: 99%
“…The combination of substance abuse, chronic stress, and altered cardiovascular function over a lifetime can be detrimental to health and ultimately lead to premature mortality. Ample studies report an association between higher neuroticism and an increased risk of all-cause mortality (Batty, Jokela, Kivimaki, & Shipley, 2016;Chapman, Fiscella, Kawachi, & Duberstein, 2009;Christensen et al, 2002;Denollet, Sys, & Brutsaert, 1995;Mroczek, Spiro III, & Turiano, 2009;Murberg, Bru, & Aarsland, 2001;Ploubidis & Grundy, 2009;Read, Vogler, Pedersen, & Johansson, 2006;Shipley, Weiss, Der, Taylor, & Deary, 2007;Terracciano, Löckenhoff, Zonderman, Ferrucci, & Costa Jr., 2008;Weiss, Gale, Batty, & Deary, 2009;Wilson, Bienias, Mendes de Leon, Evans, & Bennett, 2003;Wilson et al, 2005;Wilson, Mendes de Leon, Bienias, Evans, & Bennett, 2004). Higher levels of neuroticism have also been found to predict cause-specific cardiovascularrelated mortality (Hagger-Johnson et al, 2012;Jokela, Pulkki-Råback, Elovainio, & Kivimäki, 2013;Murberg et al, 2001;Shipley et al, 2007).…”
Section: Personality and Mortality Riskmentioning
confidence: 99%